Analisis Hukum terhadap Sanksi kepada Penyidik Kepolisian yang Tidak Segera Menyerahkan Berkas kepada Penuntut Umum dalam Perkara dengan Kualifikasi Ringan - Alfarobbi, Kevin Ariel; Ubaidillah, Lutfian U (Lembaga Pengembangan Kinerja Dosen, 2025)
The Indonesian criminal justice system upholds the principle of legal certainty to ensure the protection of the rights of all parties involved in legal proceedings. One of the recurring issues is the ambiguity regarding the timeframe for Investigators to submit case files to Public Prosecutors, particularly in minor offense cases. Article 110 of the Indonesian Criminal Procedure Code (KUHAP) merely states the word